2012
DOI: 10.1111/j.1365-2788.2012.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy from the perspective of clients with mild intellectual disabilities: a qualitative investigation of process issues

Abstract: The supportive aspects of therapeutic relationships were particularly important to participants undergoing CBT. The clinical implications are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…We are unable to determine whether or not this reflects the participants' own difficulties in comprehending and utilising these more complex strategies, the confidence of the lay therapists in delivering these more abstract components of the programme or the shorter time available to assimilate these elements of the programme. However, adults with intellectual disabilities who received individual CBT sessions delivered by clinical psychologists in a previous qualitative study also failed to recall any specific cognitive strategies, 190 suggesting that this problem is not attributable specifically either to lay therapists or to time constraints, and may reflect the intrinsic difficult of the cognitive components of CBT for people with intellectual disabilities.…”
Section: Wider Impacts Of the Interventionmentioning
confidence: 97%
See 3 more Smart Citations
“…We are unable to determine whether or not this reflects the participants' own difficulties in comprehending and utilising these more complex strategies, the confidence of the lay therapists in delivering these more abstract components of the programme or the shorter time available to assimilate these elements of the programme. However, adults with intellectual disabilities who received individual CBT sessions delivered by clinical psychologists in a previous qualitative study also failed to recall any specific cognitive strategies, 190 suggesting that this problem is not attributable specifically either to lay therapists or to time constraints, and may reflect the intrinsic difficult of the cognitive components of CBT for people with intellectual disabilities.…”
Section: Wider Impacts Of the Interventionmentioning
confidence: 97%
“…A qualitative study of individual CBT similarly reported that participants valued the opportunity to talk about their problems, experienced the process of being listened to as validating, and were helped by positive therapeutic relationships characterised by warmth, empathy and ease. 190 This has implications for the selection, training and supervision of lay therapists, as discussed further below.…”
Section: Use Of Mixed Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive behavioural interventions have been found effective [59][60][61][62] and acceptable [63] across a number of psychological conditions in people with mild intellectual disabilities. Mindfulness-based cognitive behavioural therapy (CBT) was found helpful in adults with intellectual disabilities, anxiety and depression [64].…”
Section: Trans-diagnostic Effects Of Traumamentioning
confidence: 99%